The Brittle to Ductile Transition in Polycrystalline Ice under Tension. - Schulson,Erland M. (1983)
The tensile strength of equiaxed and randomly oriented ice Ih decreases with increasing grain size and with increasing temperature. The strength of fine-grained aggregates (i.e. of aggregates finer than a critical grain size) is controlled by the stress to propagate cracks. The strength of coarse-grained material is controlled by the stress to nucleate cracks.